Convergencia mediática en la cobertura de eventos locales del diario La Prensa en su sitio web. Periodo junio-diciembre de 2023 - Molina Lucero, Alex Javier (2025)
: Media convergence in communication outlets has transformed how news is produced and consumed locally. This research analyzes media convergence in the coverage of local events by La Prensa newspaper on its website, specifically during the June–December 2023 period in Riobamba. The main objective is to analyze how media convergence is integrated into the coverage of social, cultural, sports, and other events to evaluate its effectiveness in enhancing user experience while identifying the strategies and tools employed by the outlet. Both theoretical and empirical sources were used to support this research, combining classical references with current data on digital journalism and transmedia communication. The applied methodology incorporates qualitative and quantitative approaches, using content analysis, semi-structured interviews with experts, and surveys targeting the local audience. This approach allowed for a deeper exploration of transmedia storytelling, multimedia integration, and user interactivity in the outlet's coverage. The results reveal an uneven implementation of media convergence, with better use of multimedia elements in the coverage of sports and cultural events. However, other events, such as religious and academic ones, need more technological integration and engagement strategies. For instance, [specific examples of technological integration and engagement strategies needed]. Furthermore, challenges were identified in planning, technological infrastructure, and staff training, affecting digital publications' quality and reach. In conclusion, media convergence has the potential to enrich the informational experience and strengthen the connection between local media and their audiences. However, its success depends on adopting a strategic approach that includes ongoing staff training and improvements in digital tools. This study not only highlights the need for these strategic improvements but also motivates all stakeholders to contribute to the enhancement of local news coverage. It underscores the need to develop a cohesive and dynamic digital ecosystem to enable La Prensa to optimize its impact on the community.